(Inter)subjectivity in the research pair: Countertransference and radical reflexivity in organizational research. (July 2021) - Duncan, Carrie M.; Elias, Sara R. S. T. A.
Destabilizing what we know, a central tenet of critical reflexive research, is difficult without making unconscious assumptions, beliefs, and emotions available for thought, articulation, and questioning. Articulating countertransference, a technique borrowed from psychoanalysis, informs our efforts to raise awareness of the unconscious dimensions of field experiences and thus foster radical reflexivity. Bridging the literatures on reflexivity and relational psychoanalysis, we develop a new four-dimension method of writing and analyzing fieldnotes— observing, capturing the story, articulating countertransference, and developing interpretations —that foregrounds unconscious dimensions of experience. We make visible the fieldnotes we generated during an organizational study. In doing so, we demonstrate how a research pair working together in real time can become aware of their intersubjective processes, fold together multiple dimensions of experience (conscious and unconscious), and co-construct a shared understanding of organizational dynamics. This article is valuable because it demonstrates how psychoanalytic concepts can be mobilized by psychoanalytically informed, but not formally trained, organizational researchers.